Female Masculinity Representation in Still Sick Yuri Manga : Indonesian Perspective - Anindita, Rizki Maulana; Yuwono, Ardian Indro (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2023)
Indonesia has an enormous manga audience and fans. One of the known genres is Yuri, a lesbian romance story. As a country with many Muslims who practice some Islamic customs, it is not surprising that this genre is often seen as controversial since it conflicts with moral teachings and is labeled as an LGBTQ+ normalization space. However, to not see the genre objectively is also a waste since it represents the actual life of women, especially lesbians, in a heteronormative society that glorifies androcentric capitalistic patriarchal ideology—something we also usually see in Indonesia. Therefore, the Yuri genre is a counter-narrative to Japanese and Indonesian society. Using Barthes’ semiology with Janet Chafetz’s seven traits of masculinity, we analyzed the representation of female masculinity and lesbian traits in the Still Sick manga to decode the representation of a lesbian’s female masculinity in Yuri manga. This article offers a new perspective on this discriminated genre. It shows that entertainment media bears criticism against its society while helping the public, especially domestic hobbyists, understand Yuri manga and its female masculinity more. Five points can be discussed in this article: 1) the shakaijin Yuri theme reconstructs the girls’ love genre and masculinity in manga and anime, 2) the negotiated power relation between lesbian households, 3) women’s hybrid ikigai acts as a critique against the masculine counterpart, and 4) critic against the heteronormative-homophobic society through the representation of lesbian life in Japan. The comparison between Japanese and Indonesian popular culture is also discussed to understand the context.